PENGGUNAAN DEBARYOMYCES SP. DAN SCHIZOSACCHAROMYCES SP. DENGAN ADJUVANT UNTUK PENGENDALIAN PENYAKIT ANTRAKNOSA PADA MANGGA - Dian Indratmi (Jurnal Gamma, 2009)
The aimed of this research to find out the effectifity some adjuvant to enhance Debaryomycessp. and Schizosaccharomyces sp. actifity as agens biocontrols against anthracnose pathogen C.gloeosporioides on mango.The laboratory experiment included testing adjuvant conferral for enhance anthracnose diseaseobstruction on mango. The experiment with Complete Randomized Design and 3 replication. Therewere 13 treatment,it’s A1 = control (only pathogen); A2 = yeast Debaryomyces sp. ; A3 = yeastSchizosaccharomyces sp.; A4 = yeast Debaryomyces sp.+ Schizosaccharomyces sp.(mixture); A5 =Debaryomyces sp. + Tween 1 %; A6 = Schizosaccharomyces sp. + Tween 1 %; A7 = mixture yeast+ Tween 1 %; A8 = Debaryomyces sp. + CaCl2 2%; A9 = Schizosaccharomyces sp. + CaCl2 2%;A10 = mixture yeast + CaCl2 2%; A11 = Debaryomyces sp. + Trehalose 2%; A12 =Schizosaccharomyces sp. + Trehalose 2%; A13 = mixture yeast + Trehalose 2%.Results of the experiment indicated Debaryomyces sp. and Schizosaccharomyces sp. yeast insingle or mixtures with or without adjuvant to be able to grow on mango fruit surface, and effectiveinhibited development of the anthracnose disease caused of C. gloeosporioide on mango fruit thatshown with significantly reduced lesion size and incubation periods 4 days longer.